Playable Experiences at AIIDE 2016 - Zook, Alexander; Cook, Michael; Butler, Eric; Siu, Kristin; Guzdial, Matthew; Riedl, Mark; Ryan, James; Samuel, Ben; Summerville, Adam; Mateas, Michael; Wardrip-Fruin, Noah (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2016)
The AIIDE Playable Experiences track celebrates innovations in how AI can be used in polished interactive experiences. Four 2016 accepted submissions display a diversity of approaches. Rogue Process combines techniques for medium-permanence procedurally generated hacking worlds. Elsinore applies temporal predicate logic to enable a time-traveling narrative with character simulation. A novel level generator uses conceptual blending to translate Mario Bros. design styles across levels. And Bad News uses deep simulation of a town and it's residents to ground a mixed-reality performance. Together these playable experiences showcase the opportunities for AI in interactive experiences.